2019
DOI: 10.1029/2019jb018702
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular Clay Films Control Inelastic Deformation in the Groningen Gas Reservoir: Evidence From Split‐Cylinder Deformation Tests

Abstract: Production of oil and gas from sandstone reservoirs leads to small elastic and inelastic strains in the reservoir, which may induce surface subsidence and seismicity. While the elastic component is easily described, the inelastic component, and any rate‐sensitivity thereof remain poorly understood in the relevant small strain range (≤1.0%). To address this, we performed a sequence of five stress/strain‐cycling plus strain‐marker‐imaging experiments on a single split‐cylinder sample (porosity 20.4%) of Slochter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 109 publications
2
31
0
Order By: Relevance
“…d denotes the assumed grain contact flaw spacing in 2-D, chosen to be equivalent to the characteristic interspacing of grain contact surface irregularities seen in micrographs; µ denotes the assumed friction coefficient of the intergranular illite; B is a constant describing the consolidation behavior of illite; E q is the Young's modulus of quartz grains; Y is the fracture energy of quartz and φ cr is the intragranular porosity fraction assumed to prevail after multi-edge cracking Pijnenburg et al (2019a, b) shows that these graincontact clay films are thicker in the more porous sandstones. Roughly estimating these thicknesses from the micrographs (Pijnenburg et al 2019a) or split-cylinder (Pijnenburg et al 2019b) samples deformed up to stages 1, 3d or 3c (refer Fig. 1).…”
Section: Key Microstructural Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…d denotes the assumed grain contact flaw spacing in 2-D, chosen to be equivalent to the characteristic interspacing of grain contact surface irregularities seen in micrographs; µ denotes the assumed friction coefficient of the intergranular illite; B is a constant describing the consolidation behavior of illite; E q is the Young's modulus of quartz grains; Y is the fracture energy of quartz and φ cr is the intragranular porosity fraction assumed to prevail after multi-edge cracking Pijnenburg et al (2019a, b) shows that these graincontact clay films are thicker in the more porous sandstones. Roughly estimating these thicknesses from the micrographs (Pijnenburg et al 2019a) or split-cylinder (Pijnenburg et al 2019b) samples deformed up to stages 1, 3d or 3c (refer Fig. 1).…”
Section: Key Microstructural Observationsmentioning
confidence: 99%
“…8.1.3). A simple analysis shows that compaction by intergranular slip plus clay consolidation is virtually time or rate insensitive at effective stresses pertaining to the current state of depletion of the Groningen reservoir (σ 1 = 57 MPa; σ 3 = 27 MPa), so that reservoir compaction by these mechanisms is expected to be similarly time or rate insensitive (Pijnenburg et al 2019b). In accordance with this, long-term compaction experiments performed on the Slochteren sandstone over weeks (Pijnenburg et al 2018) to months (Hol et al 2015) at similar stresses, temperature (100 °C) and chemical conditions (4 M salt brine) to those seen in the Groningen field showed that the bulk of stage 2 inelastic compaction is instantaneous, while decelerating creep deformation contributed a modest 10-20% to the inelastic strain accumulated during active loading.…”
Section: Implications: Improved Basis To Assess Experimental Data Appmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Groningen reservoir lies close to its maximum burial depth (Gaupp and Okkerman, 2011), and because long-term clay consolidation depends mainly on effective normal stress (Brown et al, 2017), intergranular clay films compacted during burial would almost certainly deform further as the effective vertical stress increased from ∼30 to 57 MPa during depletion of the Groningen reservoir. As demonstrated by Pijnenburg et al (2019b), such stress changes are sufficient to inelastically compact individual 2-5-µm-thick intergranular clay films in the Slochteren sandstone by ∼4%, i.e., by 0.1-0.2 µm. Coupled with the intergranular sliding (clay film shearing) required by the in situ condition of 1-D vertical strain, this implies reservoir compaction strains of 0.1-0.2% for typical detrital grain sizes of 100-200 µm (Pijnenburg et al, 2019b).…”
Section: Discussionmentioning
confidence: 87%